In-class Exercises Regarding the Roles of Excipients in a Pharmaceutics Course - Eytan Klausner (University of Minnesota Libraries Publishing, 2023)
Objective: To assess student perceptions regarding: 1) exercises designed to enhance student comprehension of the roles of pharmaceutical excipients in dosage forms and 2) the use of resources to identify the roles of excipients. Description: In-class exercises regarding the roles of excipients were implemented in a foundational pharmaceutics course. The exercises covered the topics of liquid single-phase systems, liquid multiphase systems, drug delivery to the skin, and parenteral, ophthalmic, and nasal dosage forms. Students were introduced to resources to identify the roles of excipients. The exercises included the presentation of pharmaceutical preparations with various fundamental excipients, followed by student polling and class discussion. A survey was administered to evaluate student perceptions regarding the exercises about the roles of excipients and the use of resources to identify the roles of excipients. Findings: Eighty students participated in the study (response rate = 99%). Student perceptions indicated that the exercises helped them understand the material better and enhanced their performance in the non-sterile compounding course taught concurrently with the pharmaceutics course. Students indicated that the resources they used during the exercises were lecture notes from the course (95%), lists with excipients that the instructor provided (24%), a Web search, e.g., Google, Bing (20%), the sixth edition of the Handbook of Pharmaceutical Excipients (18%), Micromedex/Martindale (16%), and the International Journal of Pharmaceutical Compounding (6%). Conclusion. Targeted excipient exercises are a practical approach to enhance student understanding and can be utilized in pharmaceutics and non-sterile compounding courses across various pharmacy curricula.